NATION-BUILDING DI THAILAND: INTEGRASI NASIONAL DI WILAYAH UTARA (LANNA) - , BISMA PUTRA SAMPURNA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Thailand has been indicated to be successful to integrate its northern region (Lanna) since mid 20th century with an assimilation approach. People who live there are now assimilated culturally, economically and politically. Studies showed that number of resistance toward the process of integration conducted by the Thai Government on the northern area tend to be the lowest compared to the north eastern and southern region. With the majority of the people dominated by native Lanna, this circumstance tends to be an anomaly within the form of national integration. However, this region used to be an independent territory of Lanna Kingdom for six centuries before Siam attempted to annex it on late 18th century and integrated it on the early 20th century. This thesis will try to examine two things. First, seeking the national integration method that used by the Thai Government by looking to its integration policy. Secondly, measure the degree of success of the integration that conducted in the northern region (Lanna), within three categories, which are social, economic and political. The method that used to conduct the research is through interview experts and review studies. The result will be useful to help categorizing how success is Thai Government on conducting national integration in Lanna.